Variations in Clinical Presentation of Acute Hepatitis in Children - Nasir, Muhammad; Ammar Athar, Muhammad; Kumari, Geeta; Ahmed, Syed Taha; Bin Khalid, Mazen; Saleem, Satwat (Journal of Neonatal Surgery, 2025)
Back ground and Objective: When it comes to public health issues, acute viral hepatitis (AVH) in children is a worldwide and developing-country issue. This study was carried out to identify the clinical and epidemiological spectrum of AVH in children caused by infection with hepatitis A virus (HAV) and hepatitis E virus (HEV). Study Design: Cross-sectional Place and Duration: The study was conducted at Bahria Medical College Karachi from May 2023 to May 2024. Methods: Total 77 children had age <15 years were included in this study. All the included children had signs and symptoms of acute viral hepatitis. After taking informed written consent, detailed demographics included age, sex, duration of illness and socioeconomic status were recorded.Blood sample was taken for the assessment of HAV IgM and HEV IgM using an enzyme-linked immunosorbent assay (ELISA). SPSS 24.0 was used to analyze all data. Results: There were 43 (55.8%) males and 34 (44.2%) female children among all cases. Mean age of the children was 5.9±3.24 years. Low socioeconomic status was found in 44 (51.9%) cases. Frequency of fever was 62 (80.5%), jaundice in 60 (77.9%), abdominal pain in 50 (64.9%), followed by nausea, yellowness of the eyes, loss of apetite and dark colored urine. We found thatHAV in 55 (71.4%) cases. Frequency of liver transplant found in 5 (6.4%) patients. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) was significantly higher among all cases. There was no any mortality found among all cases. Conclusion: We found higher cases of acute AVH in this study. Acute viral hepatitis disproportionately impacted males between the ages of 6 and 10, those from lower and moderate socioeconomic backgrounds, and those who drank water that had not been cleaned.